Effect of Board and Audit Committee Characteristics on Profitability: Evidence from Pharmaceutical and Chemical Industries in Bangladesh - Hasan, Mohammad Tariq; Molla, Mohammad Shahansha; Khan, Fahim (Finance & Economics Review, 2019)
Purpose: The objective of this study is to investigate the relationship between corporate governance (CG) elements, namely board characteristics (board size, independence, expertise) and audit committee characteristics (audit committee size, independence, expertise) with profitability, present by two proxy ROA and ROE. Method: This study includes all listed firms of DSE in Bangladesh under the category of pharmaceutical and chemical industry, i.e. total 31 firms for 3 years from 2015/16 to 2017/18 means 93 firm year observations. Theoretical model of the study is framed under agency theory. This study applied panel data set in regression model Using Fixed-Effects with Driscoll and Kraay’s Standard Errors to test the hypothesis by STATA 13 software. The study model also consider two control variables: firm size and leverage according to literature. Results: Empirical result of the study presents that board size, board expertise and audit committee size have significant positive relationship with both proxy of profitability i.e. ROA and ROE. Moreover, audit committee expertise has significant negative relationship with ROA but insignificant relationship with ROE. However, all other variables does not have significant influence on profitability. Implications: This study will extend the literature of CG and profitability in an emerging economy like Bangladesh. Agency problem can be solved with more vigilant practice of CG. This study could be extended further by considering all listed firm of DSE which will give us more insight of CG practice in Bangladesh.